Using online discussion forums to promote student engagement in an academic literacies course - Fouché , Ilse; Kimani, Wacango; Nkosi, Hlengiwe (Journal for Language Teaching, 2022)
The advent of Covid-19 forced universities worldwide to find ways of presenting content online that would otherwise have been facilitated in a face-to-face environment. A first-year literacy course at a South African university servicing a large number of B.Ed. students had traditionally relied on class discussions and small group work for clarification of concepts as well as the development of student writing. Online learning, however, made these practices very challenging, and subsequently online discussion forums were identified as a “second prize” way of achieving course outcomes that had traditionally happened in person. To our surprise, the online forums had affordances for the development of academic literacies, promoting student engagement and providing feedback that we had not anticipated. To investigate the reasons for this, focus group discussions were held with students. The feedback received from these focus group interviews confirmed our suspicion that online discussion forums must remain an integral part of our academic literacy course, even after all Covid-19 restrictions are lifted.